2010
DOI: 10.1101/cshperspect.a003749
|View full text |Cite
|
Sign up to set email alerts
|

The X as Model for RNA's Niche in Epigenomic Regulation

Abstract: SUMMARYThe X-linked region now known as the "X-inactivation center" (Xic) was once dominated by protein-coding genes but, with the rise of Eutherian mammals some 150 -200 million years ago, became infiltrated by genes that produce long noncoding RNA (ncRNA). Some of the noncoding genes have been shown to play crucial roles during X-chromosome inactivation (XCI), including the targeting of chromatin modifiers to the X. The rapid establishment of ncRNA hints at a possible preference for long transcripts in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 125 publications
(169 reference statements)
1
52
0
Order By: Relevance
“…Finally, long noncoding RNAs usually acting in cis (on the chromosome or the local region where they were synthesized) can turn off gene expression by attracting proteins that modify chromatin structure. The effect can spread to an entire chromosome, in the case of the Xist RNA that condenses one of the two X chromosomes in female mammals and thereby gives gene dosage compensation (Lee 2010). In other cases, the effect is more local, affecting transcription of a single gene or a group of genes (Wang et al 2010).…”
Section: The Contemporary Rna Worldmentioning
confidence: 99%
“…Finally, long noncoding RNAs usually acting in cis (on the chromosome or the local region where they were synthesized) can turn off gene expression by attracting proteins that modify chromatin structure. The effect can spread to an entire chromosome, in the case of the Xist RNA that condenses one of the two X chromosomes in female mammals and thereby gives gene dosage compensation (Lee 2010). In other cases, the effect is more local, affecting transcription of a single gene or a group of genes (Wang et al 2010).…”
Section: The Contemporary Rna Worldmentioning
confidence: 99%
“…Many groups have reported that ncRNAs recruit the PRC2 complex and direct silencing to relevant regions of the chromosome. Extensive studies on the roles of ncRNA in X inactivation center (XIC), 44 gene expression from Hox clusters, 45 and imprinted loci revealed that segments of ncRNA bind the PRC2 complex and regulate its activity and localization.…”
Section: Ncrna and Prc2 Recruitmentmentioning
confidence: 99%
“…Previous reports have shown that lncRNAs have multifunctional roles in modulating embryonic pluripotency, differentiation, development and various diseases, particularly in cancer (11)(12)(13). lncRNAs may be classified according to their mode of action and their functions in cells, including genetic imprinting (14,15), modulating the cancer epigenome (9), serving as molecular decoys (16) and post-transcriptional regulation (10). Accumulating evidence has shown that lncRNA expression profiling may facilitate the diagnosis and prognosis of human cancer, including bladder cancer (17), leukemia (18), breast cancer (9) and rectal cancer (19), suggesting that lncRNAs may serve as effective therapeutic targets for intervention.…”
Section: Introductionmentioning
confidence: 99%